2017
DOI: 10.3389/fpsyg.2017.01884
|View full text |Cite
|
Sign up to set email alerts
|

Self-Presentation Strategies, Fear of Success and Anticipation of Future Success among University and High School Students

Abstract: The backlash avoidance model (BAM) suggests women insufficiently self-promote because they fear backlash for behavior which is incongruent with traditional gender roles. Avoiding self-promoting behavior is also potentially related to associating success with negative consequences. In two studies we tested whether self-promotion and fear of success will be predictors of lower salaries and anticipation of lower chances of success in an exam. In study 1, prior to the exam they were about to take, we asked 234 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…The observation that women were more likely to rate vocalizers as relatively stronger than were men at the same actual difference in strength is consistent with a general tendency for women to underestimate, and for men to overestimate, their skills and abilities ( Bleidorn et al., 2016 , Ehrlinger and Dunning, 2003 , Erkut, 1983 , Freund and Kasten, 2012 , Gold et al., 1980 , Kosakowska-Berezecka et al., 2017 , Syzmanowicz and Furnham, 2011 ). Of particular interest is that women correctly identified relatively weaker male vocalizers on only 25% of trials, and tended to judge similar strength male vocalizers as stronger than themselves.…”
Section: Discussionsupporting
confidence: 74%
“…The observation that women were more likely to rate vocalizers as relatively stronger than were men at the same actual difference in strength is consistent with a general tendency for women to underestimate, and for men to overestimate, their skills and abilities ( Bleidorn et al., 2016 , Ehrlinger and Dunning, 2003 , Erkut, 1983 , Freund and Kasten, 2012 , Gold et al., 1980 , Kosakowska-Berezecka et al., 2017 , Syzmanowicz and Furnham, 2011 ). Of particular interest is that women correctly identified relatively weaker male vocalizers on only 25% of trials, and tended to judge similar strength male vocalizers as stronger than themselves.…”
Section: Discussionsupporting
confidence: 74%
“…These include rating the task difficulty of an engagement task high and downrating the confidence for their responses due to conservative self-presentation strategies, such as presenting oneself as attempting to perform at the best of their ability. Previous research has also suggested that certain participants downrate task difficulty and overstate their response confidence to come across as overachievers (Hellmann, 2016; Kosakowska-Berezecka et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We present a force pressure measuring device disguised as a mouse pad. The device was designed to assess physiological responses in tasks that varied in difficulty (Hellmann, 2016; Kosakowska-Berezecka et al., 2017). The device was also applied to assess the association between self-reports for response confidence and click-release time and force pressure (Hellmann, 2016; Kosakowska-Berezecka et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be that students were threatened by the creativity element of the module, and this manifested in a pessimistic score prediction, potentially also as a protective self-presentational strategy. 56,57 Nevertheless, an increased correlation between postintervention predictions and marks obtained for the intervention module (Table 3), suggest the intervention may help students link learning activities to learning outcomes and performance. Students performed better than they had expected to at the start of the semester, also supporting the intervention's effectiveness of 'coaching up' students' creative abilities.…”
Section: Areas For Further Considerationmentioning
confidence: 99%